Analyzing the Application of UTAUT2 Model in Predicting the Adoption of Electronic Shopping in Nigeria - Kumar, Pawan; Usman, Muhammad Umar (Indian Journal of Marketing, 2024)
Purpose : Electronic shopping has become a global phenomenon with a significant impact on the economy. Previous studies have examined the factors affecting electronic shopping adoption using the unified theory of acceptance and use of technology (UTAUT2) in various countries. But in Nigeria, there are either very few or none at all. This study evaluated the UTAUT2 model and added two new elements to close this gap. Methodology : The study was descriptive and cross-sectional, and a purposive sampling approach was used to select a sample of 477 online shoppers. A survey questionnaire was used to collect data, and partial least squares (PLS) were used to analyze the data. Findings : The results of this study showed that the most important variables impacting behavioral intention were effort expectancy, enabling situations, hedonic incentive, habit, trust, and technology awareness. Price, social impact, and performance expectations, however, were not much valued. User behavior was influenced by trust and behavioral intention but not by enabling circumstances, habit, or technological knowledge. Practical Implications : The findings of this study have important ramifications for future researchers, retailers, marketing managers, and legislators. Originality : This experiment is distinctive since it is the first to incorporate technology awareness and trust into the UTAUT2 model in the context of online buying. By creating a study model from a Nigerian cultural perspective, the survey increased our previous understanding of technological adoption.